Outcome of laparoscopic cholecystectomy in acute and chronic cholecystitis. - Khattab, Omar S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: laparoscopic cholecystectomy is standard treatment in gallbladder disease. Acute cholecystitis has been relative contraindication of laparoscopic cholecystectomy. With the accumulation of experience in laparoscopic surgery, laparoscopic cholecystectomy is being gradually applied for the treatment of acute cholecystitis Objective: to evaluate and compare the outcome of laparoscopic cholecystectomy in acute and chronic cholecystitis in terms of complications, conversion rates, reason of conversion, need for special modifications of the operative technique, and hospital stay. Methods: A prospective study done Between April 2007 and January 2010, in the department of general surgery, medical city teaching hospital, Baghdad. Evaluation of all patients admitted with symptomatic gall bladder disease, who underwent laparoscopic cholecystectomy were included in this study. They were classified as group A (having acute cholecystitis) and group B (having chronic cholecystitis), The diagnosis of AC was based on clinical, ultrasonographic, and operative finding; also histological diagnosis. Results: A total of 197 patients. 46 (23%) had acute cholecystitis (group A) while 151 patients (76.6%) had chronic cholecystitis (group B). In group A, Gall bladder decompression was required in 4 (8.7%) patients. One patient (2.2%) had wound infection, and one patient (2.2%) developed a subhepatic biliary collection. While epigastric port hernia occurs in one patient (2.2%). In group B, One patient (0.7%) had wound infection, and one patient (0.7%) had umbilical port hernia. Conversion rate was 3(6.5%) for group A and 0% for group B. There was no procedure related mortality in either group. The hospital stay (6-24 hours) was the same for both groups (group A; mean 9.13±6.89 hours, group B; mean 15.77±8.99 hours). Conclusion: laparoscopic cholecystectomy is safe in all patients presented with symptomatic gall bladder disease.